Prevalence of metabolic syndrome among children with psoriasis in urban Bengaluru - H V Shree Lakshmi; Leelavathy Budamakuntla; C M Shyam Sundar (Wolters Kluwer Medknow Publications, 2023)
Background: Psoriasis is a common, chronic inflammatory dermatosis that often has its onset during childhood. There is increasing evidence that psoriasis in adults is associated with obesity, metabolic syndrome (MetS), and associated comorbidities. Such an association raises concern with regard to the long-term health implications for children with psoriasis and suggests that better awareness, evaluation, and management of overweight and obese patients and associated metabolic disease are warranted in this population. Objectives: The present study was undertaken to evaluate the prevalence of MetS in childhood psoriasis. Materials and Methods: It was a cross-sectional, observational study in children aged between 6 and 18 years with psoriasis involving >10% body surface area. All children were evaluated and investigated for MetS. Results: The study included 32 children, female-to-male ratio was 5:3 with an earlier presentation in females. Body mass index was >75th centile in eight children, and among them, four had >90th centile. The waist circumference of four children was in the 90th percentile for age. Mean fasting plasma glucose, serum triglycerides, and serum high-density lipoprotein (HDL) were 89.81 ± 6.56 mg/dl, 109.25 ± 36.29 mg/dl, and 37.78 ± 7.40 mg/dl, respectively. Four of 32 children met the criteria for MetS, 14 others had at least one criterion. Fifty percent (16/32) of them had HDL lower than 40 mg/dl. The mean duration of psoriasis was more in those with MetS (4.75 years vs. 1.44 years, P = 0.005). Conclusion: Pediatric psoriasis is found to be associated with obesity and MetS. The presence of obesity with psoriasis mandates evaluation for MetS.